Prediction of Hydro-mechanical Stability of Dam: Using Calibrated Model from Back Analysis and Monitoring Data - Samad Narimani; Seyed Morteza Davarpanah; Javad Sattarvand (Civil Engineering Journal, 2016)
Earth-fill dam safety and stability control during service period is important at the view point of economics and social security. Monitoring is very important to control dam security, to compare real action with predicted planning and to make good experience and opportunity for future planning. In this paper, water pore pressure and settlements in different parts of Sattarkhan dam during service period was studied. So at first, according to instrument data installed in the body of dam, calibration of numerical model done and by doing back analysis real properties of materials of dam defined. Then by using the calibrated model, pore water pressures and settlements of dam studied. Analysis carried out by Flac2D Finite Difference software. The constitutive model used was Mohr-Coulomb at the state of plane strain. Results showed that dam will be safe during service period at the view point of hydro-mechanical behaviour. Finally, stability of dam studied from the view of rapid depletion of the reservoir, which results showed safety conditions.